2007
DOI: 10.1007/s10350-007-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase is Coexpressed with Cox-2 in Sporadic Colorectal Cancer: A Correlation with Advanced Stage

Abstract: Our study demonstrates that 5-lipoxygenase is expressed in colorectal adenocarcinomas in association with cyclooxygenase-2 expression. Moreover, an elevated expression of this enzyme seems to be significantly correlated with tumor aggressiveness. Further studies would clarify the need for target therapies inhibiting both metabolic pathways in such tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Similar results were obtained in a study examining 12-LO mRNA levels between breast cancer tissue and matched normal tissue, and additionally 12-LO levels were found to correlate with tumour staging [24]. Similar to 12-LO, 5-LO is reportedly overexpressed in a number of cancer tissues including prostate, renal, breast, colorectal and pancreatic tumours compared to normal tissues [25,26,27,28,29]. A number of pharmacological inhibitory studies have also indicated a regulatory role of 5-LO in cancer cell proliferation and growth [25,30,31].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were obtained in a study examining 12-LO mRNA levels between breast cancer tissue and matched normal tissue, and additionally 12-LO levels were found to correlate with tumour staging [24]. Similar to 12-LO, 5-LO is reportedly overexpressed in a number of cancer tissues including prostate, renal, breast, colorectal and pancreatic tumours compared to normal tissues [25,26,27,28,29]. A number of pharmacological inhibitory studies have also indicated a regulatory role of 5-LO in cancer cell proliferation and growth [25,30,31].…”
Section: Introductionsupporting
confidence: 74%
“…In a study of colon adenomas ( n = 111), 5-LO expression was found to correlate with typical high risk factors for malignant transformation to colorectal adenocarcinoma, suggesting its usefulness as a biomarker in early detection of this cancer type [58]. Additionally, in a small study of 55 sporadic colorectal adenocarcinomas, a positive correlation of 5-LO was found with tumour stage and lymph node metastasis [29]. …”
Section: 5-lipoxygenase Pathway In Cancermentioning
confidence: 99%
“…These scores have been referred to in several published reports. ( 19–21 ) The sum of the intensity and percentage counts was used as the final score. Tumor COX‐2 expression was analyzed both qualitatively and quantitatively.…”
mentioning
confidence: 99%
“…From animal models and in vitro studies, it is evident that expression of 5-LOX appears to be occasionally up-regulated during neoplastic transformation [59]. Expression of 5-LOX is characterized in early stage of colon carcinogenesis and is up-regulation of 5-LOX in colonic adenomatous polyps and CRC [60,61]. These observations suggest that 5-LOX plays a role in CRC development and may be an early target for chemoprevention of CRC.…”
Section: Loxmentioning
confidence: 96%